Apu Wood (Pistia stratiotes) as Phytoremediation Agent of Screen-printing Wastewater - Sulastri, Aini; Kadaria, Ulli; Jumiati, Jumiati; Nugraheni, Putranty Widha (Advances in Tropical Biodiversity and Environmental Sciences; Vol 7 No 1 (2023): ATBESDO - 10.24843/ATBES.2023.v07.i01.p04, 2023)
Abstract . The screen-printing process produces wastewater like organic compounds that are difficult to degrade and heavy metals such as chromium, copper, manganese, and lead, which are toxic and can accumulate in the human body through the food chain. Phytoremediation is one method that utilizes plants' ability to reduce organic and inorganic pollutants, including heavy metals. Objective : This study aimed to describe the concentration of screen-printing waste that can be tolerated by apu wood plants and analyze the effectiveness of apu wood as a heavy metal remediator. Technology or Method : The method used in this research is a combination of filtration and phytoremediation using apu wood to reduce heavy metals such as Pb and Cr, 6+ and a preliminary test of Pb and Cr 6+ contained in the screen-printing wastewater was carried out. Results: Apu wood lives and thrives on screen-printing wastewater, with an average of 34 new individuals' tillers growth within 15 days. The propagation of apu wood in screen-printing wastewater produced total biomass with an average of 145 grams per reactor. The effectiveness of apu wood as a remediator of Pb was 13.65%, and accumulated in the leaves was 0.0911 mg/L. The accumulation of Cr 6+ in the leaves was 0.6635 mg/L. The Cr 6+ component in the waste during 15 days of treatment did not show a positive effect on metal removal because the higher chromium element oxidation reaction occurred in the wastewater during the research process. Keywords Apu wood; chromium (VI); filtration; phytoremediation.